Testosterone to estrogen conversion is not responsible for the vasodilating effects of testosterone ex vivo - Tan, Shijin; Yi, Dong; Zhu, Wei; Sun, Rong; Wei, Meng (Cellular and Molecular Biology, 2018)
Men have a higher incidence of cardiovascular disease, but poorer vasodilatation than women. However, testosterone exerts vasodilating actions ex vivo. We aimed to determine if reactive oxygen species (ROS) produced in vivo could cause ‘eNOS uncoupling' that accounts for the disparity between in vivo and ex vivo results. Ovariectomized SHR and WKY rats were divided into 3 groups: untreated, estradiol benzoate (EB) treated, and testosterone propionate (TP) treated. EB and TP rats were treated for 8 weeks, and blood pressure, serum estrogen, progesterone, and testosterone were measured. Rats were euthanized and aorta samples were taken for examination of nitric oxide, phosphorylated eNOS (p-eNOS), H2O2, gr91phos, and pAkt. Mesenteric arterial rings were used in myographic studies of endothelium dependent and independent vasorelaxation. The influence of testosterone added to the bathing solution of rings from testosterone-supplemented rats with/without an eNOS inhibitor, with/without blockade of androgen or estrogen receptors, and with/without an inhibitor of gp91phox was examined. Treatment with testosterone for 8 weeks did not change endothelium-dependent relaxation in response to acetylcholine in the presence or absence of the eNOS inhibitor L-NAME, or in the presence or absence of blockade of the androgen receptors, estrogen receptors, or gp91phox. No change in nitric oxide, p-eNOS, pAkt, or gp91phos of the aorta was noted. A significant increase in H2O2 was seen in testosterone-supplemented SHR rats, but this was not accompanied by eNOS uncoupling. These results suggest that conversion of testosterone to estrogen is not responsible for its vasodilating effects seen ex vivo.